Platelet sequestration and activation during GalTKO.hCD46 pig lung perfusion by human blood is primarily mediated by GPIb, GPIIb/IIIa, and von Willebrand Factor. (18th May 2016) - Burdorf, Lars; Riner, Andrea; Rybak, Elana; Salles, Isabelle I.; De Meyer, Simon F.; Shah, Aakash; Quinn, Kevin J.; Harris, Donald; Zhang, Tianshu; Parsell, Dawn; Ali, Franchesca; Schwartz, Evan; et al.
Abstract: Background: Here, we ask whether platelet GPIb and GPIIb/IIIa receptors modulate platelet sequestration and activation during GalTKO.hCD46 pig lung xenograft perfusion. Methods: GalTKO.hCD46 transgenic pig lungs were perfused with heparinized fresh human blood. Results from perfusions in which αGPIb Fab (6B4, 10 mg/l blood, n = 6), αGPIIb/IIIa Fab (ReoPro, 3.5 mg/l blood, n = 6), or both drugs (n = 4) were administered to the perfusate were compared to two additional groups in which the donor pig received 1‐desamino‐8‐d ‐arginine vasopressin (DDAVP), 3 μ g/kg (to pre‐deplete von Willebrand Factor (pVWF), the main GPIb ligand), with or without αGPIb (n = 6 each). Results: Platelet sequestration was significantly delayed in αGPIb, αGPIb+DDAVP, and αGPIb+αGPIIb/IIIa groups. Median lung "survival" was significantly longer (>240 vs. 162 min reference, p = 0.016), and platelet activation (as CD62P and βTG) were significantly inhibited, when pigs were pre‐treated with DDAVP, with or without αGPIb Fab treatment. Pulmonary vascular resistance rise was not significantly attenuated in any group, and was associated with residual thromboxane and histamine elaboration. Conclusions: The GPIb‐VWF and GPIIb/IIIa axes play important roles in platelet sequestration and coagulation cascade activation during GalTKO.hCD46 lung xenograft injury. GPIb blockade significantly reduces platelet activation and delays platelet sequestration in this xenolung rejection model, an effect amplified by adding αGPIIb/IIIa blockade or depletion of VWF from pig lung.